A cosmetic treatment based on the secretion of Cryptomphalus aspersa 40% improves the clinical results after the use of nonablative fractional laser in skin aging. (21st June 2019) - Truchuelo, M. Teresa; Vitale, Maria
Abstract: Introduction: The main purpose of this study was to evaluate whether the application of a cosmetic treatment based on the secretion of Cryptomphalus aspersa (SCA) enhances the clinical results, tolerance, and skin regeneration after nonablative laser treatment in patients with moderate photoaging. Methods: Randomized, double‐blind, split‐face trial in 20 patients with moderate aging. Two sessions with fractional nonablative laser were performed, and the cosmetic treatments (SCA 40% on one hemiface and vehicle on the other) were applied immediately after laser session and daily during the study (28 days). Tewameter, Cutometer, Visioscan, VisioFace, photography, dermoscopy, and clinical evaluation were assessed. Side effects were also evaluated. Results: A significant decrease in the density of microcolumns (25%, 71%, 32%, and 61% less density, respectively, at T3 P = 0.008, T7 P = 0.002, T22 P < 0.001, and T24 P < 0.001) was observed on the side treated with SCA compared to the vehicle‐treated side. Cutaneous elasticity, area of wrinkles, and hydration on the SCA‐treated side also showed a significant improvement compared to the vehicle‐treated side. Both the researcher and patients observed a significant improvement on the side treated with SCA compared to the vehicle‐treated side. Significantly fewer side effects (erythema, burning, and dryness) were also detected. Conclusion: A cosmetic product with SCA 40% applied immediately after laser and for a period thereafter enhances and accelerates repair of damage produced by the laser and significantly reduces related adverse effects. In addition, SCA treatment could improve clinical results. In conclusion, we suggest that SCA enhances the effectiveness of laser in the treatment of cutaneous aging.